The Front-end of Large Public Projects Paradoxes and Ways Ahead - Williams, Terry M.; Samset, Knut; Volden, Gro Holst (Routledge Frontiers in Project Management, 2022)
Large public projects represent major complex investment and whilst there has been much written about how to develop, manage and deliver such projects, practice still does not match up with expectations. In this book, researchers from the Norwegian Concept Research Programme explore the paradoxes between theory and practice in collaboration with experts in the field of project governance. This book delves into the reality of large public projects, to show how they can be managed effectively and efficiently, recognising the realities of their context. It offers a range of practical conclusions as to the paradoxes of the governance and management of public projects. The international spectrum of authors draw their examples from the UK, Norway, Canada, France, Australia and the Netherlands. Bridging the gap between research, theory and practice, this book will benefit academics and researchers in the field of project management and corporate governance as well as those in the practice of public project governance, civil servants and industry practitioners.